Guidelines for Public Debt Management. (Manuals and Guides, 2001)
These guidelines assist policymakers at all levels in considering reforms to strengthen the quality of their public debt management and reduce their countries' vulnerability to international financial shocks. Vulnerability is often greater for smaller and emerging market countries because their economies may be less diversified, have a smaller base of domestic financial savings and less-developed financial systems, and be more susceptible to financial contagion through the relative magnitudes of capital flows. As a result, these guidelines should be considered within a broader context of the factors and forces affecting a government's liquidity more generally and the management of its balance sheet.